Norwegian general practitioners' collaboration with municipal care providers - a qualitative study of structural conditions - Sissel Steihaug; Bård Paulsen; Line Melby (Taylor & Francis Group, 2017)
Purpose: The purpose of this study was to explore the structural mechanisms that facilitate or counteract collaboration between general practitioners (GPs) and other providers of municipal healthcare. Good collaboration between these actors is crucial for high-quality care, especially for persons in need of coordinated services. Material and methods: The study is based on semistructured interviews with 12 healthcare providers in four Norwegian municipalities: four GPs, six nurses and two physiotherapists. Results: GPs are key collaborating partners in the healthcare system. Their ability to collaborate is affected by a number of structural conditions. Mostly, this leads to GPs being too little involved in potential collaborative efforts: (i) individual GPs prioritize with whom they want to collaborate among many possible collaborative partners, (ii) inter-municipal constraints hamper GPs in contacting collaboration partners and (iii) GPs fall outside the hospital-municipality collaboration. Conclusions: We argue a common leadership for primary care services is needed. Furthermore, inter-professional work must be a central focus in the planning of primary care services. However, a dedicated staff, sufficient resources, adequate time and proper meeting places are needed to accomplish good collaboration.